Familial florid Cemento‐osseous dysplasia – case report and review of literature. Issue 12 (6th November 2015) - Thorawat, Amit; Kalkur, Chaitra; Naikmasur, Venkatesh G.; Tarakji, Bassel
Key Clinical Message: Familial Florid cemento‐osseous dysplasia is a very uncommon condition. Cemento‐osseous dysplasia is totally asymptomatic in many cases, in those conditions, lesions are detected in a radiograph taken for other purposes. In this report, we describe a family in which mother and daughter exhibited clinical, radiographic, and histologic features of florid cemento‐osseous dysplasia. Abstract : Familial Florid cemento‐osseous dysplasia is a very uncommon condition. Cemento‐osseous dysplasia is totally asymptomatic in many cases, in those conditions, lesions are detected in a radiograph taken for other purposes. In this report, we describe a family in which mother and daughter exhibited clinical, radiographic, and histologic features of florid cemento‐osseous dysplasia.